Preparation and thermal properties of polyacrylonitrile/hexagonal boron nitride composites - ÇAKMAKÇI, EMRAH; KAHRAMAN, MEMET VEZİR; MADAKBAŞ, SEYFULLAH (ELSEVIER SCIENCE BV, 2013)
Polyacrylonitrile is a thermoplastic polymer with unique properties and it has several uses. However its flammability is a major drawback for certain applications. In this study it was aimed to prepare polyacrylonitrile (PAN)/hexagonal boron nitride (h-BN) composites with improved flame retardancy and thermal stability. Chemical structures of the composites were characterized by FTIR analysis. Thermal properties of these novel composites were analysed by TGA and DSC measurements. Glass transition temperatures and char yields increased with increasing h-BN percentage. Flame retardancy of the PAN composite materials improved with the addition of h-BN and the LOI value reached to 27% from 18%. Furthermore, the surface morphology of the composites was investigated by SEM analysis. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: PAN; h-BN; Flame retardancy; LOI; Thermal analysis; NANOCOMPOSITES; MORPHOLOGY